The Occupational Safety and Health Law in Malaysia: The Way Forward - Jamaluddin, Siti Zaharah (Journal of Malaysian and Comparative Law, 2010)
The Occupational Safety and Health Law is an important aspect of industrialisation. Malaysia has recognized its importance by enacting Ordinances way back before it obtained its independence. Changes were made to the Ordinances and the Acts to suit the needs of the growing nation. Starting with a very prescriptive and technical Ordinances and Statute, Malaysia subsequently adopted a Statute that emphasises on self-regulation, consultation and cooperation between the relevant parties with the introduction of the Occupational Safety and Health Act 1994. This article was aimed to look at the existing legal framework which governs the occupational safety and health law in Malaysia, its problems and how Malaysia can move forward in the future.